Differences and Similarities of Photocatalysis and Electrocatalysis in Two-Dimensional Nanomaterials: Strategies, Traps, Applications and Challenges - Qian, Weiqi; Xu, Suwen; Zhang, Xiaoming; Li, Chuanbo; Yang, Weiyou; Bowen, Chris R.; Yang, Ya (Nano-Micro Letters, 2021)
Photocatalysis and electrocatalysis have been essential parts of electrochemical processes for over half a century. Recent progress in the controllable synthesis of 2D nanomaterials has exhibited enhanced catalytic performance compared to bulk materials. This has led to significant interest in the exploitation of 2D nanomaterials for catalysis. There have been a variety of excellent reviews on 2D nanomaterials for catalysis, but related issues of differences and similarities between photocatalysis and electrocatalysis in 2D nanomaterials are still vacant. Here, we provide a comprehensive overview on the differences and similarities of photocatalysis and electrocatalysis in the latest 2D nanomaterials. Strategies and traps for performance enhancement of 2D nanocatalysts are highlighted, which point out the differences and similarities of series issues for photocatalysis and electrocatalysis. In addition, 2D nanocatalysts and their catalytic applications are discussed. Finally, opportunities, challenges and development directions for 2D nanocatalysts are described. The intention of this review is to inspire and direct interest in this research realm for the creation of future 2D nanomaterials for photocatalysis and electrocatalysis. Highlights: 1 This review focuses on the differences and similarities of photocatalysis and electrocatalysis in the latest 2D nanomaterials. 2 Strategies and traps for performance enhancement of 2D nanocatalysts are highlighted. 3 Challenges, future directions and applications for new photocatalysis and electrocatalysis exploiting 2D nanomaterials are suggested.